Temperature Variation Studies with Candida Antarctica Lipase B using Single Molecule Recognition Force Microscopy - Nicolaou, Charlotte (University of Sheffield, 2014)
Atomic force microscopy (AFM) is an imaging technique that can provide high resolution images of a surface as well as information on a number of mechanical properties such as elasticity, deformation and adhesion. This final parameter can be exploited to measure the rupture force between two binding molecules in a procedure known as single molecule recognition force microscopy (SMRFM). One molecule is attached to the AFM tip and used to image the second molecule. This process has been applied to many areas including drug research, materials science and biochemistry. The main purpose of this work was to use SMRFM to investigate the enzyme Candida Antarctica Lipase B (CAL B) as it shows potential for cool water washing detergents. By eliminating the need for heating, energy can be saved which is imperative in the world today. A major challenge in SMRFM is the chemistry used to bind the molecules to the tip. Therefore the first step towards studying CAL B was to use the binding pair of avidin and biotin to recreate previous experiments and confirm that the selected chemistry was appropriate. These experiments reproduced similar forces for avidin and biotin as published results. The system was then applied to measure the rupture force between CAL B and the carboxylic ester ±-2-acetoxypropionic acid at room temperature. It was found that unbinding events could be successfully observed and that leaving the AFM tip to dwell on the substrate for 100 ms produced significantly more specific events. Next a cooling device that could reduce the temperature of the AFM environment was created. The temperature was varied between 29.3oC and 7.4oC. It was found that the binding probability of CAL B increases notably at the lowest temperatures to 0.1096 ± 0.002 which further strengthens the potential for CAL B as a component for cool water detergents.